Progression from Sustained BK Viruria to Sustained BK Viremia with Immunosuppression Reduction Is Not Associated with Changes in the Noncoding Control Region of the BK Virus Genome. (4th June 2012) - Memon, Imran A.; Parikh, Bijal A.; Gaudreault-Keener, Monique; Skelton, Rebecca; Storch, Gregory A.; Brennan, Daniel C.
Abstract : Changes in the BK virus archetypal noncoding control region (NCCR) have been associated with BK-virus-associated nephropathy (BKVAN). Whether sustained viremia, a surrogate for BKVAN, is associated with significant changes in the BK-NCCR is unknown. We performed PCR amplification and sequencing of (1) stored urine and (2) plasma samples from the time of peak viremia from 11 patients with sustained viremia who participated in a 200-patient clinical trial. The antimetabolite was withdrawn for BK viremia and reduction of the calcineurin inhibitor for sustained BK viremia. DNA sequencing from the 11 patients with sustained viremia revealed 8 insertions, 16 transversions, 3 deletions, and 17 transitions. None were deemed significant. No patient developed clinically evident BKVAN. Our data support, at a genomic level, the effectiveness of reduction of immunosuppression for prevention of progression from viremia to BKVAN.